Leitura de histórias em quadrinhos do PNBE 2012 : a Turma do pererê - Buffon, Eliana Cristina (My University, 2015)
Based on a study on Ziraldo´s book A Turma do Pererê: 365 dias na Mata do Fundão, this piece of work presents some reflection on the language used in comic books (or comic strips). The book above mentioned was chosen for this study because it is part of 2012´s Library in the School National Program (PNBE 2012), a range of books aimed at the early years of Elementary School in Brazil. The study means to carry out an analysis on enunciation procedures used in the construction of the work, and which can be analyzed in the context of schooled reading, meaning to contribute to students´ literacy learning process. The research can be justified on the fact that students tend to present poor reading skills, as shown in assessments made public about this area, on the complexity of the cultural products aimed at the young reader, and, besides, on the insertion of comic strips in the PNBE range of books. The investigation follows the Education, Language and Technology approach, and it is part of the Post-Graduation in Education Program of the Caxias do Sul University (PPGEd/UCS). It is also part of a research project called “Challenges and welcomings in children´s literature: the mediation of the literary reading”, which has been approved by FAPERGS and which means to study the books that have been short-listed to make up the PNBE range of books for the early years of Elementary Education. Among the authors whose ideas have contributed to the research there are: Mikhail Bakhtin (2006), Lev S. Vygotsky (1998), both of which helped on reflections upon language; Will Eisner (2012), Moacy Cirne (1972, 1973, 2000), Álvaro de Moya (1993, 2002), Paulo Ramos (2009) and Valdomiro Vergueiro (2009), who discuss aspects of the language used in comic strips; Brian Street (1984), with his studies on literacy, and Joseph Schwarcz (1982), who elaborates on the role played by illustration on children´s books, among others. The study is organized in chapters, which contemplate (a) the relations between education and language, considering the school as a space for literacy; (b) the methodological processes of the research, and (c) an analysis of the work and indication of the elements present in the making up of the title, which should be taken into consideration in the mediation of literary reading. It was the analytical description of aspects of the work chosen that guided the method, aiming to pinpoint the procedures used in the construction of this discursive modality present in the Brazilian schools´ libraries. As a result, it stands out in the studied corpus that comic books contemplate themes that make it possible to identify the student with the expressed conflict, as it presents situations that are present in daily life and that there are instances in the way the narrative is enunciated which need to be taken into consideration when mediated reading is proposed in the school environment. Last but not least, one highlights the importance of teachers being familiar with the language used in comic strips, besides its specificity as a genre so as to make it possible for them to contribute for the students´ literacy.
Este estudo apresenta uma reflexão sobre a linguagem na modalidade narrativa denominada história em quadrinhos, a partir do estudo do livro A Turma do Pererê: 365 dias na Mata do Fundão, de Ziraldo. O referido título foi selecionado para estudo por pertencer ao acervo do Programa Nacional Biblioteca da Escola de 2012 (PNBE 2012), destinado aos anos iniciais do Ensino Fundamental. A pesquisa contempla a análise de procedimentos verbo-visuais empregados na construção do título e que deveriam ser apreciados em situação de leitura escolarizada, a fim de contribuir para o letramento dos estudantes. A investigação justifica-se em virtude do baixo desempenho da capacidade de leitura de estudantes, conforme resultados de avaliações de desempenho, da complexidade dos produtos culturais direcionados ao leitor mirim e, ainda, da inserção de histórias em quadrinhos nos acervos do PNBE. A investigação insere-se no Programa de Pós-Graduação em Educação da Universidade de Caxias do Sul – PPGEd/UCS, na linha de pesquisa Educação, Linguagem e Tecnologia e é parte integrante do projeto de pesquisa “Desafios e acolhimentos da literatura infantil: a mediação de leitura literária”, aprovado pela FAPERGS, que objetiva estudar obras selecionadas para compor acervos dos anos iniciais do Ensino Fundamental do PNBE. Entre teóricos que subsidiam a pesquisa, destacam-se: Mikhail Bakhtin (2006) e Lev S. Vygotsky (1998) com reflexões sobre linguagem; Will Eisner (2012), Moacy Cirne (1972, 1973, 2000), Álvaro de Moya (1993, 2002), Paulo Ramos (2009) e Valdomiro Vergueiro (2009) com aspectos da linguagem dos quadrinhos; Brian Street (1984) e Soares (2010, 2013), com estudos sobre letramento, entre outros. O estudo está organizado em capítulos, discorrendo acerca de (a) relações entre educação e linguagem, considerando a escola como espaço de letramento; (b) processos metodológicos da pesquisa e (c) análise da obra e indicação de elementos presentes na composição do título, que deveriam ser considerados na mediação de leitura literária. A metodologia pautou-se na descrição analítica de aspectos da obra selecionada, a fim de apontar procedimentos empregados na construção dessa modalidade discursiva presente nas bibliotecas escolares brasileiras. Como resultados, destacamos, a partir do corpus estudado, que as histórias em quadrinhos contemplam temas que possibilitam a identificação do estudante com o conflito posto, por apresentar situações presentes no cotidiano e que há constâncias no modo de enunciação das narrativas que precisam ser consideradas em propostas de leitura mediada no ambiente escolar. Alertamos, ainda, para a necessidade de o professor ter conhecimento acerca da linguagem dos quadrinhos e sua especificidade como gênero, a fim de contribuir para o letramento dos estudantes.
Keywords: A Turma do Pererê (obra literária); Histórias em quadrinhos; Literatura infantil; Leitura; Letramento; A Turma do Pererê (Literary work); Comic books, strips, etc.; Children's literature; Reading; Literacy